Some physical properties and Vickers hardness measurements of Fe diffusion-doped Bi1.8Pb0.35Sr1.9Ca2.1Cu3Oy superconductors - Ozturk, O. (Springer Science and Business Media LLC, 2011)
In this study we have investigated the influence of iron diffusion and diffusion-annealing time on the mechanical and the superconducting properties of bulk Bi1.8Pb0.35Sr1.9Ca2.1Cu3Oy superconductors by performing X-ray diffraction (XRD), scanning electron microscopy (SEM), Vickers hardness, dc resistivity (ρ-T) and critical current density (Jc) measurements. The samples are prepared by the conventional solid-state reaction method. Doping of Bi-2223 was carried out by means of iron diffusion during sintering from an evaporated iron film on pellets. Then, the Fe layered superconducting samples were annealed at 830 °C for 10, 30 and 60 h. The mechanical properties of the compounds have been investigated by measuring the Vickers hardness (Hv). The mechanical properties of the samples were found to be load dependent. The load independent Vickers hardness (H0), Young’s modulus (E), yield strength (Y), and fracture toughness (KIC) values of the samples are calculated. These all measurements showed that the values of the Vickers hardness, critical current density, and critical transition temperature and lattice parameter c increased with increasing Fe doping and diffusion-annealing time.